Competition and Fundamental Rights. (8th July 2015) - Oliver, Peter; Bombois, Thomas
Abstract: This survey covers the case law of the Luxembourg and Strasbourg courts on fundamental rights and competition law, together with fundamental rights cases that do not directly concern competition law but are likely to have an impact on it. In her View on the draft Agreement on accession to the European Convention on Human Rights, AG Kokott dismissed the suggestion that it would jeopardize the mechanisms for enforcing Articles 101 and 102 TFEU, whereas in Opinion 2/13, the Court of Justice found the draft Agreement repugnant to the EU Treaties on other grounds. In his Opinion in Huawei, AG Wathelet grappled with the question as to when, despite Article 47 of the Charter, seeking interim relief with respect to alleged infringements of standard-essential patents ('SEPs') constitutes an abuse of a dominant position. In Grande Stevens, the European Court of Human Rights delivered a very important judgment on the principle of ne bis in idem .